Modification of Microbial Fuel Cell Anodes via Nitric Acid and Hydrogen Peroxide Treatment for Electrogenic Biofilm Formation - Gladysheva M.S.; Molodkina N.R. (Problems of the Regional Energetics, 2025)
The primary objectives of this study are to evaluate the influence of modifying carbon felt electrodes on the formation of microbial electrogenic biofilm and the efficiency of bioelectrogenesis in a two-chamber microbial fuel cell. Microbial fuel cells represent an alternative energy technology that enables the conversion of organic matter into electricity through microbial metabolism. However, their practical application has been limited by low energy efficiency and instability. This research aims to enhance the efficiency of microbial fuel cells by modifying the anodes, which may contribute to the broader adoption of these systems within sustainable energy development. To achieve these objec-tives, the following tasks were addressed: modification of anodes using a mixture of HNO₃ and H₂O₂ to improve the hydrophilic properties and biocompatibility of the electrode surface; long-term re-cording of the system's output voltage to assess the dynamics of electricity generation and to establish correlations between biofilm formation stages and output voltage; and analysis of biofilm structures using light and scanning electron microscopy. Key findings include quantitative indicators of output voltage from two microbial fuel cell configurations. The system with the modified anode demonstrated a significant advantage, exhibiting an output voltage 2.70 to 2.75 times higher than that of the system with untreated carbon felt. The significance of these results lies in confirming the effectiveness of the electrode modification method used, which may facilitate the implementation of microbial fuel cells as alternative energy sources for low-power autonomous devices.